Response of PIP aquaporins to long-term cold stress in two citrus rootstocks - Amparo Primo-Capella; Mary-Rus Martínez-Cuenca; Emma García-Hiltner; María Ángeles Forner-Giner (PLoS ONE, 2026)
Cold is one of the most impactful abiotic stresses causing significant crop losses. Additionally, it is a major limiting factor, reducing cultivation areas, especially for tropical and subtropical species such as citrus. In this study, we conducted a physiological assessment of water balance, photosynthesis, fluorescence, and transcriptomic data, to further understand the response of aquaporins in the Valencia Delta Seedless variety grafted onto two rootstocks: Citrus macrophylla and Carrizo citrange, considered sensitive and tolerant rootstocks, respectively. After 6 weeks of exposure to 1°C with a photoperiod of 16 hours of light and 8 hours of darkness, measurements were taken of CO 2 assimilation rate, stomatal conductance, substomatal CO 2 concentration, transpiration rate, and photosynthetic apparatus damage (Fv/Fm). In addition, plant water balance was quantified by measuring water potential (Ψw), osmotic potential (Ψπ), and relative water content (RWC%). Finally, gene quantification was performed for three previously selected aquaporins ( PIP1–2, PIP2–2, and PIP2–5 ), which our laboratory has formerly associated with cold acclimation and, consequently, with tolerance. Cold temperatures lead to stomatal closure, reduced transpiration, and a significantly decreased osmotic potential (Ψπ), like what occurs under conditions of extreme drought, as the plant seeks to prevent water loss through transpiration. However, the stem water potential (Ψw) and relative water content (RWC) often remain at levels typical of actively growing plants under adequate irrigation conditions. Gene expression and physiological results suggests that plants grafted onto Carrizo citrange rootstock exhibit a better cold response and increased acclimation, leading to the overexpression of aquaporins PIP1–2 , PIP2–2 , and PIP2–5 .